Significance of Nutritional-Inflammatory Index as Predictors for Total Neoadjuvant Therapy-Induced Tumor Regression in Locally Advanced Rectal Cancer Patients - Zhao Z; Yan M; Pang H; Chen L; Tang X; Chen Z; Chen X; Sun H (Dove Medical Press, 2024)
Zhou Zhao,1,2,* Menghua Yan,1,* Huayang Pang,1,2 Lihui Chen,1 Xi Tang,1 Zhixiong Chen,1 Xiufeng Chen,1 Hao Sun1 1Gastrointestinal Cancer Center, Chongqing University Cancer Hospital, Chongqing, 400030, People's Republic of China; 2Chongqing Key Laboratory of Translational Research for Cancer Metastasis and Individualized Treatment, Chongqing University Cancer Hospital, Chongqing, 400030, People's Republic of China*These authors contributed equally to this workCorrespondence: Hao Sun; Xiufeng Chen, Gastrointestinal Cancer Center, Chongqing University Cancer Hospital, No. 181 of Hanyu Road, Chongqing, 400030, People's Republic of China, Email sunhao_med@cqu.edu.cn; sunhao68@sina.com; 13028399392@163.comPurpose: To evaluate the predictive capacity of the nutritional-inflammatory index and clinicopathological characteristics in patients with locally advanced rectal cancer (LARC) receiving total neoadjuvant therapy (TNT).Methods: Data from 127 patients with LARC receiving TNT from January 2017 to January 2021 were retrospectively analyzed. Clinicopathological characteristics with different TNT-induced responses were compared. The Chi-square test and the Mann-Whitney test were used to analyze the association between pre-TNT factors and TNT-induced responses. Multivariable logistic regression analysis was used to construct a predictive model.Results: In the cohort of 127 patients with LARC who underwent total neoadjuvant therapy (TNT), the mean age was 54.1 ± 11.4 years; 88 (69.3%) were male. Seventy patients (55.1%) exhibited a favorable response to TNT, while 57 patients (44.9%) demonstrated a poor response. Tumor characteristics, including diameter, distance from the anal verge, pre-TNT lymphocyte, pre-TNT hemoglobin, CA199, PLR, and HALP, exhibit correlations with TNT-induced tumor regression. Multivariate logistic regression analysis identified large tumor diameters (> 5.0 cm; p = 0.005, HR 2.958; 95% CI 1.382- 6.335) and low HALP (≤ 40; p = 0.002, HR 0.261; 95% CI 0.111- 0.612) as predictors of TNT-induced poor responses. Additionally, low levels of HALP were associated with an increased risk of recurrence in patients with LARC with TNT, but this was not statistically significant (p = 0.087, HR 2.008, 95% CI 0.906- 4.447).Conclusion: A large tumor diameter and low HALP predict poor tumor regression induced by the CAPOX-based TNT regimen in patients with LARC.Plain Language Summary: Recent studies have shown that total neoadjuvant therapy (TNT) is becoming a key treatment for some people with advanced rectal cancer. However, there's still a lot we do not know about what affects how well patients respond to this treatment. The aim of this study was to see if certain nutritional and inflammatory measures, along with other clinic characteristics, can predict how well patients with advanced rectal cancer will respond to TNT. We looked back at medical records from 127 patients who received TNT between 2017 and 2021. We examined how certain pre-treatment factors were linked to patients' responses to the therapy. Certain tumor characteristics and blood test results were connected to how well the tumors responded to treatment. Specifically, patients with larger tumors (over 5 cm in diameter) and lower levels of a specific blood marker called HALP were more likely to have a poor response to treatment. Although low HALP was also linked to a higher chance of the cancer coming back, this result was not strong enough to be certain about.Keywords: Rectal cancer, Total neoadjuvant therapy, HALP, Tumor regression